Disc haemorrhage is associated with the fast component, but not the slow component, of visual field decay rate in glaucoma. Issue 11 (2nd July 2014) - Kim, Joon Mo; Kyung, Haksu; Azarbod, Parham; Lee, Jun Mo; Caprioli, Joseph
Abstract : Background/aims: To investigate the association of disc haemorrhage (DH) with regional visual field (VF) decay in glaucoma. Methods: Retrospective longitudinal study was performed. Patients from the University of California, Los Angeles, glaucoma database were assigned to two groups based on the presence or absence of a DH. Pointwise exponential regression was used to identify the fast and slow rate components of VF decay. Associations between patient demographics, ocular and systemic factors, and visual field rates were analysed. Results: A total of 185 patients were included, 54 of whom were documented to have a DH at some point during their course. DH group had a higher female preponderance (p=0.017, OR 2.23), a higher incidence of peripapillary atrophy (p=0.002, OR 4.46), more advanced disease (p=0.016) and a higher fast rate component of VF decay (p<0.001) than non-DH group. With multivariate logistic regression analysis, only the fast rate component showed a statistically significant relationship with DH. Conclusions: The presence of DH is associated with a greater fast component rate of VF decay. The identification and monitoring of the fast component of VF decay may prove useful in the identification and management of glaucoma patients at high risk of progression.